Analysis of Export Development Potential for Virgin Coconut Oil as a Flagship Regional Product in the International Market - Awaluddin, Sri Prilmayanti; Muntasir, Muntasir; Imran, Un Dini; Kamaluddin, La Ode Amijaya; Thalib, M Kurniawan (Journal of Economic Education and Entrepreneurship Studies, 2024)
This study aims to analyze the potential for developing the export of Virgin Coconut Oil (VCO) from Sulalam Topejawa as a flagship regional product of Takalar Regency. The study employs a qualitative approach using a case study method to deeply explore internal and external factors influencing VCO exports. Data collection methods include in-depth interviews, direct observations, document analysis, and comparative studies with other countries such as the Philippines and Sri Lanka. The results show that although global demand for VCO continues to increase, Sulalam VCO still faces significant challenges, including low production standards, lack of international certification, traditional production technology, and weak global branding and marketing strategies. On the other hand, the product has advantages such as abundant local raw material availability, high health value as a natural product, and significant potential for product diversification. Strategies to enhance competitiveness can be carried out through improving production standards and obtaining international certifications such as USDA Organic and HACCP, optimizing global supply chains, implementing aggressive digital marketing, and diversifying products through innovation. Synergy between the government, private sector, and local communities is also essential for the successful development of Sulalam VCO exports. This study provides important recommendations for business actors and the government in developing the VCO industry sustainably, thereby enhancing the competitiveness of local products in the international market and positively impacting the economic well-being of the local community.